German as a foreign language in Britain: the history of German as a 'useful' language since 1600 - McLelland, Nicola (De Gruyter, 2015)
A quarter of a century ago, two essays examined the early history of German as a Foreign Language (GFL) in Britain.2 The present paper revisits the history of GFL at a time of perceived crisis in modern language education, to provide some historical answers to the question “Why learn German?” that may offer a useful context for debates about the status of German in schools and universities and in wider society today.3 Using as primary sources the materials available to learners since 1600, most of which have previously received very little attention from this perspective, I examine the interplay and the tensions between the various motivations for learning German that have been asserted, and give some illustrations of how the various answers to “Why German?” were reflected in the contents of textbooks and examinations for learners.4 Discussions of the value of German can be found in other kinds of primary sources, too, especially in the later period, including the popular and scholarly press, school prospectuses, policy documents, published and unpublished syllabi and curricula, but this study concentrates largely on the case made for German to its learners in the materials that were available to them. For the later nineteenth and twentieth centuries, however, when modern languages became institutionalized and then established in mass education, I have also made selective reference to policy documents, and to the popular and scholarly press, as these too became fora in which the value of German was discussed. We shall see that the question of why to learn German is closely related to expectations about who should learn German, and that those expectations, too, have changed; but I shall argue that cultural rather than purely instrumental reasons have remained crucial.